IMPROVING THE TECHNOLOGY OF REFINING LOCAL RAW SOYBEAN OILS UNDER THE INFLUENCE OF AN ELECTROMAGNETIC FIELD (American Journal of Interdisciplinary Research and Development, 2025)
Methods of using the influence of an electromagnetic field in the refining process of vegetable oils obtained from local soybean seeds were studied. As a result of applying electromagnetic effects of various intensities, it was achieved to increase the quality indicators of refined soybean oils, as well as to improve their physicochemical characteristics.